Interactive Physics Modular (IPM): The development of website-based learning media using a problem-based learning model and a STEM-ESD approach to enhance environmental literacy in temperature and heat topics - Afif Jauhari; Febiana Dinda Puspita; Iqbal Ainur Rizki; Sujito Sujito; Nurita Apridiana Lestari (Education and Development Research, 2026)
Environmental literacy is a key 21st-century competency that should be fostered through contextual and sustainability-oriented physics education. However, studies integrating Problem-Based Learning (PBL) and STEM-ESD into web-based learning platforms, while also mapping students’ initial environmental literacy through Rasch analysis on temperature and heat topics in Indonesia, remain limited. This study aimed to: (1) identify students’ initial environmental literacy profiles as a basis for needs analysis, and (2) develop and evaluate the initial readability of the Interactive Physics Modular (IPM). This research adopted a research and development approach using the ADDIE model and involved 78 students who had studied temperature and heat without using IPM. Data were collected through an environmental literacy essay test covering four indicators: cognitive skills, environmentally responsible behaviors, ecological knowledge, and environmental care affect. The data were analyzed descriptively and using the Rasch model. The results showed that environmental care affect achieved the highest mean score (3.85; 77%), followed by cognitive skills (3.47; 69.4%), environmentally responsible behaviors (2.60; 52%), and ecological knowledge (2.19; 43.8%). Rasch person–item analysis indicated that items requiring the integration of temperature and heat concepts with complex environmental contexts and the formulation of realistic solutions were the most difficult. Readability results showed that IPM was clear, engaging, and effective in linking physics concepts with environmental issues. This study contributes by proposing a contextual essay-based framework for assessing environmental literacy through Rasch analysis and by offering a model for integrating PBL and STEM-ESD into a website-based physics learning platform.